Identifikasi Bakteri di Ekosistem Mangrove Kecamatan Candi sebagai Agen Bioremediasi Pencemaran Logam Berat Cu, Pb, dan Hg di peraiaran Pesisir Wonorejo - Nur Hidayatullah Romadhon (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2024)
Bioremediation of heavy metals using bacteria has been widely developed due to the high accumulation of heavy metals (Cu, Pb, and Hg) in ecosystems, largely driven by industrial activities. The toxic effects of these metals on living organisms and the environment require immediate solutions through biological approaches. This study aimed to identify and analyze the potential of indigenous bacteria from mangrove sediments in Candi District as bioremediation agents for heavy metals Cu, Pb, and Hg in vitro. This research employed a descriptive-exploratory design and was conducted at the Microbiology Laboratory, Universitas Muhammadiyah Surabaya, from July to November 2023. Bacterial isolation was performed using the pour plate method and purified with the streak plate method on Nutrient Agar medium. Preliminary screening was carried out on Nutrient Agar supplemented with Cu, Pb, and Hg at concentrations of 100, 250, 350, and 500 ppm. The reduction ability of bacterial isolates was tested on Salmonella Shigella Agar (SSA) medium using the Langmuir method. Isolation of bacteria from mangrove sediments yielded nine isolates, all of which demonstrated the ability to degrade Cu, Pb, and Hg. Among them, isolate T1, identified as Pseudomonas aeruginosa (Gram-negative), exhibited the highest reduction capacity, achieving 82% for Cu, 74% for Pb, and 72.61% for Hg.